Full spectrum cannabidiol-rich extract reduced propofol dosage required for anesthetic induction in dogs—a pilot study - Hasckel Gewehr, João Lourenço; Enzele, Maria Laura; Freiria, Lucas Marlon; Nunes, Morgana Martins; Spengler, Júlia; Dondoerfer Teixeira, Ana Paula; Amazonas, Erik; Sasso Padilha, Vanessa (Frontiers in Veterinary Science, 2024)
Introduction Cannabinoids show great therapeutic potential, but their effect on anesthesia still remains unclear. Use of chronic recreational Cannabis in humans undergoing anesthetic procedures tends to require a higher dose when compared to non-users. On the other hand, studies on rodents and dogs have shown that cannabinoid agonists may potentiate certain anesthetics. This contrast of effects possibly occurs due to different time lengths of administration of different phytocannabinoids at different doses, and their distinct effects on the Endocannabinoid System, which is also affected by anesthetics such as propofol and isoflurane. Methods Twenty-seven healthy male dogs, client-owned, ranging from 1 to 7 years, and from 5 to 35 kg were selected, mean weight 15.03±7.39 kg, with owners volunteering their animals to participate in the research performed in the Federal University of Santa Catarina (UFSC). Dogs were randomized into 3 groups. The Control Group (CON, n = 9), receiving only Extra Virgin Olive Oil, the same oil-base used in the treatment groups. Group 2 (G2, n = 9) received 2 mg/kg of total phytocannabinoids, and Group 3 (G3, n = 9) received 6 mg/kg of total phytocannabinoids. All groups received their treatments transmucosally, 75 min before their induction with propofol. Heart and respiratory rate, blood pressure, temperature and sedation were evaluated prior to, and at 30, 60, and 75 min after administration of the fsCBD-rich extract or Placebo extract. Preanesthetic medication protocol was also included across all treatment groups, 15 min before induction. Parametric data was analyzed with one-way ANOVA, followed by Student–Newman–Keuls (SNK) if significant statistical differences were found. Non-parametric data was analyzed using Friedman’s test, followed by Dunn test for comparisons between all timepoints in the same group. Kruskal-Wallis followed by Dunn was utilized for between groups comparisons. Propofol dose necessary for induction was analyzed through One-way ANOVA followed by Tukey’s Multiple Comparisons Test, using Instat by Graphpad, and differences were considered statistically significant when p < 0.05. Our analysis assessed if statistical significance was present between time points in the same group, and between groups in the same time points. Results In our study, 6 mg/kg of total phytocannabinoids were able to reduce the dose of propofol necessary for induction by 23% when compared to the control group. The fsCBD-rich extract did not produce significant sedation within or between groups, although statistically significant differences in heart rate and systolic blood pressure were found. Discussion Our findings indicate that phytocannabinoids could be an adjunct option in anesthesia, although further research is necessary to better confirm this data. Additionally, further research is needed to determine the best dosage, delivery method, time for administration, ideal molecular profile for desired effects, safety, drug–drug interactions, and transurgical effects.